PHYTIC ACID (MYO-INOSITOL HEXAPHOSPHATE)- A PROMISING PHARMACEUTICAL AGENT: A REVIEW - Narayanaswamy, Radhakrishnan; Mohd Esa, Norhaizan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Phytic acid (myo-inositol hexaphosphate) has gained much attention among researchers for its therapeutic value. This review focuses on pharmacological activities of phytic acid, which have been demonstrated by pre-clinical studies. Anti-carcinogenic, antioxidant, antidiabetic, hypolipidemic, anti-angiogenic, and immunomodulation are the most extensively studied pharmacological activities of phytic acid. In addition to these, phytic acid and its derivatives also possess enzyme inhibitory activities against few key enzymes such as 5-alpha reductase, aldose reductase, cyclooxygenase, lipase, matrix metalloproteinase-2 & 9, pepsin, polyphenol oxidase, protease, Î²-secretase, tyrosinase, and xanthine oxidase were emphasized. The profound pharmacological activities of phytic acid have proven to be a good therapeutic agent and could be employed in preventing as well as treating such diseases.